FUNERAL CONTEXTS OF EARLY ICHMA OF CONDE DE LAS TORRES - Bazán Del Campo, Francisco (2008)
Our knowledge about Lima and Lurin valleys on the central cosat of Peru in the last two epochs of the middle horizon is too much fragmented, the realeased is limited just a few of ceramic, some burials and some mutilated settlements. The few dedication to this lapse is caused in part to the more atractive two first epochs of middle horizon local and regional and the highest grade of destruction of the archaeological sites of this time in the area of Lima city. This article shows a proposition about the burials practices of the fourth epoch of Middle Horizon and the beginning of Late Intermediate Period of Conde de Las Torres. It intends to show a synthesis of the burial contexts rebuilt of that moment that we called Early Ichma , wich material culture fills an empty between the finals of Middle Horizon and the beginning of the following period. Due that the nature of burials contents, this synthesis respect to pottery enphasises in the local style of the epoch more than the ceramics of foreing styles of the central coast of that time.